Caffeine for sports performance - Burke, Louise 1959-; Spriet, Lawrence L.; Desbrow, Ben (Human Kinetics, 2013)
Caffeine for Sports Performance is the definitive resource for all your questions regarding caffeine and its impact on sports performance. Based on the most recent research, studies, and guidelines, this guide is ideal for athletes and fitness enthusiasts looking to improve training and competition. Inside you will find these features: The history of how caffeine has become the most widely used drug in the world; The pros and cons of using caffeine, including habitual daily caffeine intake, to boost sports performance; Personal usage guides that can be applied to various sports or scenarios of caffeine use in training and competition; Health advice regarding caffeine use; Performance effects of caffeine use; Safety considerations and potential risks; Best and worst sources for caffeine. Caffeine for Sports Performance provides plenty of practical tips for using caffeine. In particular you will find sidebars that feature interviews with top athletes and coaches who have interesting stories to tell regarding their experiences using caffeine. You will also gain new insight into current attitudes towards caffeine and how those attitudes have changed over the years. Caffeine for Sports Performance gives you all you need to understand and use caffeine to get the most out of your sport.